Alternative Models of Electronic Literary Criticism: Intermedial and Ergodic - Tatang Iskarna (Journal of Language and Literature, 2023)
Electronic literature, known as cyber or digital literature, has elicited negative and favourable responses. Negative reactions centre on disagreements regarding its definition and the author's quality and authenticity. Positive reflexes include its rapid and massive distribution, publication, and subversion against the dominant establishment of printed literature. Its open space for creativity due to the addition of multimedia and its intensive interaction between writers and readers also become beneficial values. Despite the negative and favourable backlash, electronic literary criticism development has not yet been widely discussed. Electronic academic critique models are rarely debated due to a lack of consensus on their definitions, interdisciplinarity, and technological obstacles. This article attempts to propose alternate models for electronic literary criticism, viewing it as a new genre. This literary analysis offers alternatives based on its significant elements: technology (platform), immersive experience and interactivity (the reader’s involvement), literary work (various electronic types), and accessibility (wide range of readers). Considering that electronic literature combines literature, technology, and digital media to interpret works and investigate the relationships between technology, authorship, and readership, its criticism needs to broaden its area which includes technology. Intermedial and ergodic criticism can be the alternatives to approach this new genre.